Kinematic status of Bryan and Mobi-C artificial cervical discs post cervical hybrid surgery: a retrospective study - Yukun Ma; Yang Xiong; Ting Wang; Xing Yu; Chuanhong Li; Letian Meng; He Zhao; Yongdong Yang; Dingyan Zhao; Fengxian Wang; Yi Qu (Journal of Orthopaedic Surgery and Research)
Abstract Objective To examine the mid-term efficacy and imaging results of using the Mobi-C and Bryan implants after cervical hybrid surgery for 2-level cervical spondylolisthesis, and to observe their postoperative changes and differences in the flexion-extension center of rotation (FE-COR) for the anterior cervical disc replacement (ACDR) segment. Methods Patients who underwent cervical hybrid surgery between June 2014 and June 2019 were included in this study. The mJOA, NDI, and VAS scores were used to assess clinical outcomes, and the FE-COR of the ACDR segment was measured. Pre-operative and 36-month radiographs were collected to compare the range of motion (ROM) in the total cervical spine, ACDR segmental ROM, and operated adjacent segmental ROM. Translation distances for the Mobi-C and Bryan devices were measured. The degree of disc degeneration in the adjacent segment and bony fusion of the ACDF segment were observed. Results Eighty-one patients were included (40 in the Mobi-C group and 41 in the Bryan group). All patients showed improvements in their postoperative mJOA, NDI, and VAS scores (P < 0.05). The C2-C7 ROM decreased in both groups (P < 0.05). There was no significant decrease in ACDR segmental ROM and upper or lower adjacent segmental ROM compared with preoperatively (P > 0.05). No significant differences were found between the two groups in the above ROM measurements (P > 0.05). For the Mobi-C group, the follow-up compared with pre-surgery showed statistical significance in both FE-COR-X (44.86 ± 7.70% vs. 57.13 ± 8.45%, P < 0.05) and FE-COR-Y (52.29 ± 12.71% vs. 34.47 ± 10.32%, P < 0.05). For the Bryan group, there were no significant differences at follow-up in FE-COR-X and FE-COR-Y compared with pre-surgery (P > 0.05). No significant difference in translation distance between the two groups was observed (P > 0.05). All ACDF segments were in a stable condition. Twenty-two out of 162 adjacent segments showed imaging ASD (9 cases in the Mobi-C group and 13 cases in the Bryan group). In the Mobi-C group, there were mild cases in 6 instances and moderate cases in 3 instances. In the Bryan group, there were mild cases in 8 instances and moderate cases in 5 instances. Conclusions Cervical hybrid surgery using either the Mobi-C or Bryan artificial cervical discs can achieve satisfactory results. The FE-COR of the Mobi-C segment shifts forward and downward, while the FE-COR of the Bryan segment is relatively closer to the pre-operative condition. Changes in the FE-COR after hybrid surgery in both the Mobi-C and Bryan segments might not affect clinical outcomes.